Macrocyclic Conformational Switch Coupled with Pyridinium-Induced PET for Fluorescence Detection of Adenosine Triphosphate - Morozov, Boris S.; Gargiulo, Fabiano; Ghule, Swapnil; Lee, Dong Joon; Hampel, Frank; Kim, Hwan Myung; Kataev, Evgeny A. (Journal of the American Chemical Society, 2024)
The binding of nucleotides is crucial for signal transduction as it induces conformational protein changes, leading to downstream cellular responses. Synthetic receptors that bind nucleotides and transduce the binding event into global conformational rearrangements are highly challenging to design, especially those that operate in an aqueous solution. Much work is focused on evaluating functionalized dyes to detect nucleotides, whereas coupling of a nucleotide-induced conformational switching to a sensing event has not been reported to date. We disclose synthetic receptors that undergo a global conformational rearrangement upon nucleotide binding. Integrating naphthalimide and the pyridinium ion into the structure enables stabilization of the folded conformation and efficient fluorescence quenching. The binding of a nucleotide rearranges the receptor conformation and alters the strong fluorescence enhancement. The methylpyridinium-containing receptor demonstrated high sensing selectivity for adenosine 5′-triphosphate (ATP) and a record 160-fold fluorescence enhancement. It can detect fluctuations of ATP in HeLa cells and possesses low cytotoxicity. The developed systems present an attractive approach for designing ATP-responsive artificial molecular switches that operate in water and integrate a strong fluorescence response.
Keywords: Adenosine triphosphate; Adenosine-5-triphosphate; Cellular response; Conformational switches; Down-stream; Fluorescence detection; Fluorescence enhancement; Macrocyclics; Pyridinium; Synthetic receptors; Adenosine Diphosphate; Adenosine Triphosphate; Fluorescence; Fluorescent Dyes; HeLa Cells; Humans; Nucleotides; Positron-Emission Tomography; Protein Conformation; Receptors, Artificial; Spectrometry, Fluorescence